Pendampingan Pemilihan Ketua OSIS dan Majelis Perwakilan Kelas (MPK) Berbasis E-Voting di SMA Takhassus Al-Qur’an Sebagai Edukasi Terhadap Pemilih Pemula - Robingun Suyud El Syam; Siti Lailiyah; Prasetya Prasetya; Eko Eriyanto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The article aims to describe the assistance in the election of the OSIS chairperson and the e-voting-based Class Representative Council (MPK) at SMA Takhassus Al-Qur'an as education for novice voters. Assistance strategy through planning, implementation, and evaluation. The research concludes that e-voting-based election for OSIS and MPK SMA Takhassus Al-Qur'an leaders is an agenda in order to realize democratic education for students, especially for prospective novice voters who will exercise their right to vote in the 2024 simultaneous elections.. At that moment there were at least two examples that became media for prospective voters, 1) the election of the OSIS chairman as an introduction media for regional head elections or presidential elections, 2) the election of the Class Representative Assembly (MPK) as an introduction to the election of legislative members. The e-voting system provides many conveniences for voters because it can be opened with a mobile phone, reduces the abstention rate, prevents fraud, is more economical, transparent, effective and efficient. This system is very effectively used as education for first-time voters, as evidenced by the participation of 99.5% at the first-time voter level. The research recommends for the government to consider a general election system in Indonesia using e-voting as a solution to realizing elections that are direct, public, free, secret, honest and fair.